INTERPRETASI EKOWISATA OLEH PEMANDU WISATA (PRAMUWISATA) PADA DAYA TARIK EKOWISATA PENYU DI BALI - Made Widiantari; Anak Agung Gde Raka Dalem; I Ketut Sundra (SIMBIOSIS, 2025)
Turtle-based ecotourism is a tourism activity that involve education and its quality is related to tour guides who provide interpretation. This research was important for the better sustainability of turtle-based ecotourism. This research was conducted from November 21, 2023 to January 17, 2024. This research aimed to determine types, facilities and quality of tourist guide interpretation. The methods utilized were observation, distributing questionnaires and running interviews. The number of guides interviewed were 15 and the tourists were 65. Results of this research showed that types of interpretation utilized by turtle-based ecotourism guides were guided tour, point duty, roving interpretation, presentation, demonstration, living history, interactive, and lecture or talk. The types of interpretation which were most widely used are guided tours and lectures or talks with the percentage of 100%. The interpretation facilities used by turtle ecotourism guides were printed media, self-guiding boards, interpretation boards, visitor centers, computers, videos, slideshows, cellphone numbers, and social media (Instagram and Facebook). The most widely used interpretation facilities were interpretation boards and visitor centers, with a percentage of 100%. The percentage of interpretation quality for Turtle Conservation and Education Center (TCEC), Saba Asri, Kurma Asih and Watu Klotok guides were 91.25%, 83.35%, 89.0% and 85.02% respectively. Tourist satisfaction with the interpretation from the TCEC tour guide and from Kurma Asih were classified as very good, while from the Saba Asri guide was classified as good. Keywords: Attraction, quality of interpretation, tools for interpretation, type of interpretation, tourists